2020
DOI: 10.1111/eci.13383
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of various treatment modalities for nCOV‐2019: A systematic review and meta‐analysis

Abstract: Background: Several therapeutic agents have been investigated for treatment of novel coronavirus 2019 (nCOV-2019). We conducted a systematic review and metaanalysis to assess the efficacy of various treatment modalities in nCOV-2019 patients. Methods: A literature search was conducted before 29 June 2020 in PubMed, Google Scholar and Cochrane library databases. A fixed-effect model was applied if I 2 < 50%, else results were combined using random-effect model. Risk ratio (RR) or standardized mean difference (S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 81 publications
1
15
1
1
Order By: Relevance
“…This finding is consistent with the results of previous meta-analyses reporting a reduction in mortality in COVID-19 patients treated with TCZ added to ST in comparison with those treated with ST alone [ 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the results of previous meta-analyses reporting a reduction in mortality in COVID-19 patients treated with TCZ added to ST in comparison with those treated with ST alone [ 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Discussionsupporting
confidence: 92%
“…In another RCT on severe COVID-19, the 28-day mortality rate did not differ between remdesivir-treated patients and controls 21 ( Table 3 ). According to a meta-analysis for these two RCTs 20 , 21 , the RR for clinical recovery was 1.17 (95% CI 1.07 to 1.29) 22 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the aforementioned RCT on COVID-19 comparing a combination of lopinavir/ritonavir and umifenovir with standard treatment 34 , and in another RCT on COVID-19 comparing “lopinavir/ritonavir plus IFN-α with or without ribavirin” with “ribavirin plus IFN-α” 41 , treatment with lopinavir/ritonavir did not show superior outcomes in terms of clinical deterioration or viral clearance ( Table 3 ). In meta-analyses on COVID-19 involving two of these RCTs 34 , 40 , treatment with lopinavir/ritonavir was not associated with clinical recovery or viral clearance 22 , 42 , 43 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study at a large medical center in New York City that examined the association between hydroxychloroquine use and intubation or death of patients with Covid-19, revealed that hydroxychloroquine administration was not associated with either a greatly lowered or an increased risk of the composite end-point of intubation or death [ 99 ]. However, most recent meta-analysis studies demonstrated that hydroxychloroquine administration might cause harm in COVID-19 patients [ 100 , 101 ].…”
Section: Treatmentmentioning
confidence: 99%